2020
DOI: 10.1080/00377317.2020.1834489
|View full text |Cite
|
Sign up to set email alerts
|

Surviving Being Black and a Clinician During a Dual Pandemic:Personal and Professional Challenges in a Disease and Racial Crisis

Abstract: I CAN'T BREATHE! Social distance! I CAN'T BREATHE! Stay six feet apart! I CAN'T BREATHE! Make sure you wash your hands! I CAN'T BREATHEEEE! When can I schedule a session? The duality of being Black in America and a mental health professional during a global pandemic is stressful enough; however, coupled with a simultaneous racial pandemic, the intrapsychic, interpersonal and professional responsibilities feel incessant. This article seeks to explore the lived experiences of two Black mental health professional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 26 publications
1
11
0
Order By: Relevance
“…Other strategies for mitigating burnout and STS include limiting the hours worked per week to lessen the work-related aspect of burnout. Limiting access to media/social media could prove beneficial for Black mental health therapists (Lipscomb & Ashley, 2020). Other proactive self-care interventions, such as doing mindfulness practices, or joining professional peer groups, clinical supervision, or seeking therapy, could demonstrate positive outcomes for Black mental health therapists (Giordano et al, 2020;Posluns & Gall, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Other strategies for mitigating burnout and STS include limiting the hours worked per week to lessen the work-related aspect of burnout. Limiting access to media/social media could prove beneficial for Black mental health therapists (Lipscomb & Ashley, 2020). Other proactive self-care interventions, such as doing mindfulness practices, or joining professional peer groups, clinical supervision, or seeking therapy, could demonstrate positive outcomes for Black mental health therapists (Giordano et al, 2020;Posluns & Gall, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Higher levels of racial discrimination are associated with higher levels of trauma symptoms in Black Americans, which, potentially, places Black therapists at higher risk of burnout and STS (Chou et al, 2012;Kirkinis et al 2018). Moreover, Black therapists are navigating the same race-related stresses as their Black clients (First et al, 2020;Lipscomb & Ashley, 2020). Black therapists' perceptions and appraisals of their race-related stresses may overwhelm their ability to cope in their personal and professional settings.…”
Section: Racism and Race-related Stressmentioning
confidence: 99%
See 1 more Smart Citation
“…As another example, SLPs from majority groups can use their privilege to advocate for colleagues in marginalized groups, such as BIPOC or LGBTQIA+ and work to dismantle long-standing racist systems and barriers. Creating a sense of urgency here can include drawing attention to microaggressions (ASHA, 2020b), speaking out when marginalized colleagues are asked to participate in more service opportunities to increase diversity on a committee, or drawing attention to the mental health disparities that exists (CDC, 2020;Lipscomb & Ashley, 2020). Unreported racism is directly related to stress, anxiety, isolation, and burnout (Chaudhary & Berhe, 2020).…”
Section: Advocacymentioning
confidence: 99%
“…Within the context of race, the Centers for Disease and Control Prevention notes the mental health disparities disproportionately experienced by Black populations, with the addition of COVID-19 putting them at a higher risk for mental health challenges (Lipscomb & Ashley, 2020). Czeisler et al (2020) also found that suicide ideation was significantly higher among respondents who were from minority racial/ethnic groups.…”
Section: P a G Ementioning
confidence: 99%